2017
DOI: 10.1093/gerona/glx104
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Reduces the Impact of Aging on Behavior and Physiology in the Rapidly Aging SAMP8 Mouse

Abstract: Alzheimer's disease (AD) is rarely addressed in the context of aging even though there is an overlap in pathology. We previously used a phenotypic screening platform based on old age-associated brain toxicities to identify the flavonol fisetin as a potential therapeutic for AD and other age-related neurodegenerative diseases. Based on earlier results with fisetin in transgenic AD mice, we hypothesized that fisetin would be effective against brain aging and cognitive dysfunction in rapidly aging senescence-acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 47 publications
2
78
0
1
Order By: Relevance
“…Memory impairments, especially episodic memory, occur as a consequence of normal aging across many species, including humans and rodents. Aged mice in different strains have significantly reduced spatial learning and memory abilities, and the onset of this age effect begins at middle age (even early adulthood) and persistently progresses onwards, such as SAMP8 and Kunming mice (Cao et al, , ; Chen et al, ; Currais et al, ). Bacterial infections during pregnancy result in a systemic inflammatory reaction in mothers and can affect cognition in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Memory impairments, especially episodic memory, occur as a consequence of normal aging across many species, including humans and rodents. Aged mice in different strains have significantly reduced spatial learning and memory abilities, and the onset of this age effect begins at middle age (even early adulthood) and persistently progresses onwards, such as SAMP8 and Kunming mice (Cao et al, , ; Chen et al, ; Currais et al, ). Bacterial infections during pregnancy result in a systemic inflammatory reaction in mothers and can affect cognition in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2, and 3). Other natural CRMs, such as butein and fisetin (11,21,27,38,48,53,58,59), also inhibited T-cell activation (IC 50 = 2.8 μM and 5.2 μM, respectively) ( Figs. 1 and 3).…”
Section: Resultsmentioning
confidence: 94%
“…Tremendous studies have found that fisetin is effective in treatment of diabetic neuropathy, age-related neurodegenerative diseases and brain injury (Sandireddy et al, 2016;Chen et al, 2018;Currais et al, 2018). One important reason may be that fisetin has high brain uptake potential and BBB penetration (Maher, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Maher (2009) also found that fisetin exhibits high brain uptake potential. Fisetin can reduce cognitive deficits in old SAMP8 mice while improving impaired synaptic function, age-associated stress, and inflammation (Currais et al, 2018). However, the effect of fisetin on hyperglycemia-induced neurotoxicity has not been fully addressed.…”
Section: Introductionmentioning
confidence: 99%